Consumo de sódio em indivíduos com síndrome metabólica: um estudo baseado no teor de sódio da dieta e alimentos-fonte - Lima, Severina Carla Vieira Cunha (2018)
Objective: The study aimed at evaluating the energy intake and identifying the sodium intake and its main sources in individuals with metabolic syndrome. Methods: This is a cross-sectional study with 88 individuals with metabolic syndrome diagnosis from both sexes, adults and elderly, treated at the Endocrinology Outpatient Clinic of the Onofre Lopes University Hospital, in Natal-RN, Brazil. The consumption of energy, sodium and respective source foods were assessed using two 24-hour dietary recalls, which were analyzed in Virtual Nutri Plus®. Results and discussion: The studied population was predominantly female (72.7%), and the mean age was 49.0 (11.3) years. The most frequent comorbidities were dyslipidemia (92.0%) and arterial hypertension (76.1%). The mean energy intake was 1,664.35 (630.8) kcal/d and the mean sodium intake was 2,792.8 (866.2) mg/d, with 82.2% of the individuals presenting an intake higher than the recommended intake. Significant statistical differences were found for energy intake between the sexes (p <0.001), but not for sodium intake (p = 0.107). The use of the added salt was quite expressive in the analysis of the food consumption of this population (310 repetitions, corresponding to an average of 635.5mg of sodium). Industrialized foods presented the highest amount of sodium among the foods consumed, although few patients consuming these products were registered. Conclusion: An inadequate sodium intake was found in a significant percentage of the population, and it may have a negative impact on the health of these individuals, especially those living with hypertension, evidencing the need for a broader nutritional education action directed specifically to this population.